Tafonomia experimental sobre peixes: geobiológicas e zooarqueológicas - Gomes, Amanda Leopoldina Soares (Universidade Federal de São Carlos, 2018)
Experimental Taphonomy has assisted in the simulation and understanding of variables that affect the fidelity of paleontological and zooarchaeological records. In this experimental study was tested the role of thermal action on the decomposition of Anchoviella lepidentostole "Manjuba" in different substrates. It was observed that the precooking of carcasses tends to potentiate the initial disarticulation of their parts, even before being buried. The decomposition and preservation rates also varied according to the substrates in which the fish were buried, implying morphological transformations and loss of anatomical parts. In sand, the decomposition rate of the carcasses was higher when compared to other substrates. In clay, the specimens underwent natural compression and eventually formed molds. In this substrate, the best preservation of morphological structures occurred throughout the experiment, in comparison to the others. In soil the fragmentation of the specimens occurred. Chemical and mineralogical changes on musculature and bones were evaluated using non-destructive and / or non-invasive techniques. Spectroscopic analyzes revealed promising data for understanding diagenetic changes in bones and fish musculature. Raman spectra presented changes in intensities that may be indicative of changes in bone bioapatite. Already, elemental EDS and XRF analyzes of muscle fragments indicated variations of chemical elements, including rare earth elements at low concentrations. Geobiological signs of biomineirais provide data for environmental reconstructions and indicate the extent of diagenetic changes.
Experimental fish Taphonomy: geobiological and zooarchaeological
Keywords: Taphonomy; zooarchaeological; Raman; Tafonomia; Zooarqueologia; CIENCIAS HUMANAS::ARQUEOLOGIA::TEORIA E METODO EM ARQUEOLOGIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::PALEONTOLOGIA ESTRATIGRAFICA